Study on the right to education with special references to public private partnerships - Nilay Shukla; Ketan Desai (The Scientific Temper, 2024)
The Indian education system faces significant challenges in providing quality education to all its citizens, particularly in the context of limited government resources. Public-private partnerships (PPPs) have emerged as a critical strategy to bridge this gap, leveraging private sector participation in financing and managing educational institutions. This paper examines the evolving landscape of education under PPP models in India, focusing on the implications for the right to education. Through a comprehensive review of literature and analysis of case studies, the study explores how PPPs influence access, equity, and quality in education, while also addressing concerns related to privatization and accountability. By evaluating the successes, challenges, and policy implications of PPPs in education, this research contributes to the broader discourse on the role of private sector involvement in fulfilling the right to education in developing countries.